Mapping of snail intermediate host habitats reveals variability in schistosome and non-schistosome trematode transmission in an endemic setting - Teckla Angelo; Naima Camilla Starkloff; David James Civitello; Moses Paul Mahalila; Safari Kinung’hi (Current Research in Parasitology and Vector-Borne Diseases)
The intermediate snail host of Schistosoma haematobium, the etiological agent of urogenital schistosomiasis, serves as a critical sentinel for tracking the spread of associated disease risks. In addition to S. haematobium, Bulinus spp. snails also transmit S. bovis to cattle as well as several non-schistosome trematodes to cattle and wildlife. Identifying transmission foci of these multi-parasite hosts is critical for targeted and effective One Health intervention. We investigated 467 waterbodies in 86 villages across six districts in northwestern Tanzania. A total of 43,348 Bulinus nasutus were collected across three survey phases from November 2020 to August 2021. Across all snails, 0.63% were emitting schistosome cercariae. There was a significant increase in schistosome prevalence during the year, with a peak in the dry season (June-August 2021). Furthermore, of the 25,052 snails collected in the latter two phases (March to August 2021), 4.9% were infected with non-schistosome trematodes, exceeding prevalences of schistosomes at all spatial scales. Co-infections were uncommon, with only 0.05% of snails concurrently emitting both schistosome and non-schistosome parasites. These infection patterns were consistent across village and district levels. Waterbodies used by cattle had higher schistosome prevalence than waterbodies isolated for human use. Surprisingly, non-schistosome prevalence was equal in both of these waterbody types. This suggests that cattle have an indirect role in schistosome transmission, requiring the separation of waterbody usage between cattle and humans and extending snail control in dry season to waterbodies used by cattle. By contrast, water permanence and school proximity did not impact snail or parasite presence. Targeted interventions should focus on local water use dynamics, with attention to the potential indirect role of cattle in schistosome transmission.